The noise monitoring system of Debrecen International Airport and requirement of appointing noise protection zones, regarding to the growing air traffic - Virág, László (Acta Agraria Debreceniensis, 2013)
The Debrecen International Airport has been undergoing a significant transformation regarding to the growth of traffic and its composition. Considering the dwelling zone location of the airport we cannot avoid the possible noise pollution that it may cause, since its permanency, and growth of intensity, could be the reason of durable health deficiency. The airports’ noise pollution zones are determined, and classified by domestic, and international regulations, the measured data of the noise monitoring system, and the content of the air traffic regarding to the type of planes. Summoning all of these we recommend the D zone qualification of the airport, and the traffic daylight restriction referring to the S5 type of planes. We also advise to build up a more sophisticated and wider extended noise monitoring system.